2021
DOI: 10.21037/atm-20-2785
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of teaching efficiency between virtual reality and traditional education in medical education: a systematic review and meta-analysis

Abstract: Background: Virtual reality (VR) technology has developed rapidly in recent years and has been applied in many fields, including medical education. A meta-analysis was performed to compare the examination pass rate of medical students educated using VR and those receiving traditional education to evaluate the teaching effect of VR in medical education. Methods:The PubMed, Springer Link, Science Direct, and Wiley Online Library were searched from inception to May 2020. Articles meeting the inclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 30 publications
(41 reference statements)
2
36
2
2
Order By: Relevance
“…Recently, the effectiveness of medical education using VR has been reported. 17 However, reports on the use of VR in infection control education are limited. [12][13][14][15] VR learning of the care of COVID-19 patients consisted of hand hygiene, PPE donning and doffing, and proper specimen collection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effectiveness of medical education using VR has been reported. 17 However, reports on the use of VR in infection control education are limited. [12][13][14][15] VR learning of the care of COVID-19 patients consisted of hand hygiene, PPE donning and doffing, and proper specimen collection.…”
Section: Discussionmentioning
confidence: 99%
“…Digital models are novel instruments that have been applied in the educational field. Several studies have declared that VR models are an effective tool for learning anatomy and simulating surgery ( 8 , 11 , 14 , 15 , 17 ). Izard et al reported that the application of operational VR models of the cranium and cranial fossa helps with medical training and improves surgical skills ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional twodimensional pictures, the head-mounted VR devices enable users to view stereoscopic images in a fully immersive environment. Several studies have declared that VR models are effective tools to improve the learning of complex spatial structures because of visual advantages with fast processing, relative reliability, and parallelism (8,11,(13)(14)(15)(16)(17). However, the interactive VR experience lacks the tactile information that is crucial to effectively master the complex structures and perform the surgical operation.…”
Section: Introductionmentioning
confidence: 99%
“…While conventional mannequin-based simulation can be a useful tool, upkeep and maintenance of high-fidelity simulators is expensive, and they can be cumbersome to set up and operate [10,11]. Virtual reality (VR) is an alternative simulation methodology being used increasingly in medical training and education [12][13][14][15][16]. VR has the potential advantage of increased "immersion," the sense of being physically in the virtual space or performing a task, and has been shown to manifest physiologic stress responses akin to real life among physicians participating in resuscitation simulations [13,17].…”
Section: Introductionmentioning
confidence: 99%